ANALISIS KENDALA IMPLEMENTASI PROGRAM PENANGGULANGAN TUBERKULOSIS DI KECAMATAN MERALKABUPATEN KARIMUN - Dewi, Seri; Azwar, Azwar; Damsar, Damsar (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Karimun Regency is a coastal area where coastal coastal areas are one of the areas that have many problems, especially in the field of public health. Health problems in coastal areas are a very complex problem. Various efforts have been made by the Karimun District Health Office in improving health services and facilities, especially for tuberculosis prevention. However, overall tuberculosis cases in Meral District, Karimun Regency continued to increase from previous years. The implementation of the tuberculosis prevention program policy in Meral Subdistrict has not been carried out optimally even though tuberculosis officers in the Meral District have tried to run the tuberculosis prevention program. There are several obstacles in the implementation of pulmonary tuberculosis prevention programs including the lack of facilities and special health workers for tuberculosis, low awareness of tuberculosis sufferers to reduce tuberculosis transmission, and the patient's low knowledge of the risk of tuberculosis.